Editing, Performance, Texts New Practices in Medieval and Early Modern English Drama - Jenkins, Jacqueline; Sanders, Julie; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2014)
The essays in this volume challenge current 'givens' in medieval and early modern research around periodization and editorial practice. They showcase cutting-edge research practices and approaches in textual editing, and in manuscript and performance studies to produce new ways of reading and working for students and scholars.
Keywords: Performing arts; Theater—History.; Poetry; Theater; Literature; British literature; Performing Arts; Theatre History; Poetry and Poetics; Theatre and Performance Studies; Literature, general; British and Irish Literature